(untitled) (Indonesian Journal of Civil Engineering Study, 2025)
The increase in traffic volume at the signalized intersection on Jalan Ahmad Yani Semarang City, causes congestion that has the potential to disrupt the smooth flow of traffic. The method used is to model the existing conditions of the intersection in VISSIM, then conduct simulations to obtain performance data such as traffic volume, degree of saturation, waiting time, and vehicle delay. The results of the study indicate that high traffic volume and suboptimal traffic light cycles cause vehicle deceleration at red lights and acceleration at green lights, resulting in congestion and congestion. The current simulation shows an average queue length of 127.63 meters with a maximum queue length of 227.20 meters, and an average vehicle delay of 99.69 seconds, which is categorized as Level of Service (LOS_F), indicating very poor traffic conditions. In reducing the very bad LOS, then for next 5 years it is necessary to have recommendations that can improve traffic flow such as diverting one-way traffic flow on the arms of Jl. Ki Mangunsarkoro and Jl. East Erlangga.